An alternative definition and use for the constraint function for rule-based methods of functional regionalisation. (May 2015) - Halás, Marián; Klapka, Pavel; Tonev, Petr; Bednář, Marek
Abstract: The paper addresses the issue of the constraint function and its use in methods of regional taxonomy and assessment of regional systems. It proposes an alternative definition for the constraint function for rule-based methods of functional regionalisation, such as the delineation of local labour-market areas, including alternative conceptions of the self-containment of the regions, and the trade-off between size and self-containment. An alternative constraint function has been applied in the territory of the Czech Republic as shown in the paper's illustrative example of its use from the original CURDS algorithm.